Kikuchi-Fujimoto Disease: A Case Report and Review of literatures - Mollah, Md Abid Hossain; Sharmim, Mst Shanjida; Fatmi, LE (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2015; VOL 39 (2) :99-101